Modelling the Drivers of Impulsive Buying Behaviour: A Case of South Africa - Chinomona, Elizabeth (Journal of Economics and Behavioral Studies, 2019)
Abstract: Impulsive buying behavior is an emerging phenomenon in marketing literature and it affects consumers across the board. Impulsive buying is seen as the outcome of demonstrative reactions that breed the unexpected craving to purchase. Impulsive buying is becoming an important factor for retailers since they generate a lot of income through this kind of behavior. Due to the expansion of organized retail over the country, shops are trying to comprehend the buying behavior of consumers and try by all means that they trigger consumers to act in an impulsive way. Traditional buying behavior of consumers was seen as when purchasers made a list for purchasing products then depart to a particular store and purchase it. But now the whole buying behavior is changing due to the rise in the income level of consumers. This is giving the consumers more buying power, transformation in the socio-cultural environment way of life and consumption pattern. This, therefore, influences the consumer to act in an irrational manner which is known as unplanned buying without considering the potential consequences which may include non-usage of the product, negative economic consequences and feelings of regret, fury and fault. So the present study aims to analyze how uniqueness, price and past orientation influence impulse buying behavior are focusing on classical clothing brands like Nike, Adidas and Reebok. This study attempts to discern how consumer’s traditional planned shopping behavior is shifting to impulse buying behavior. The study used a quantitative research method and analyzed the data by means of SMART PLS to test the relationships and the model. 350 questionnaires were used for data analysis using convenience sampling process. The outcomes of the research showed a progressive and significant association between the predictors (the need for uniqueness, price and past orientation) and the outcome variable (impulsive buying behavior).